2010
DOI: 10.1007/s10765-010-0760-6
|View full text |Cite
|
Sign up to set email alerts
|

Reference Viscosity of Argon at Low Density in the Temperature Range from 290 K to 680 K

Abstract: An all-quartz oscillating-disk viscometer of very high precision was used to measure the temperature dependence of the viscosity of argon in the limit of zero density. The measurements were based on a single calibration value at 298.15 K, which was calculated theoretically using an accurate ab initio pair potential for argon and the kinetic theory of dilute gases. The uncertainty of the experimental data is conservatively estimated to be 0.15 % at room temperature increasing to 0.2 % at the highest temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 30 publications
4
31
0
Order By: Relevance
“…In addition, a comparison of our experimental argon data between 291 K and 682 K [8] and of experimental reference values obtained by May et al [19] at NIST (203 K to 394 K) with the theoretical argon values [12] showed excellent agreement within ±0.1 %. Considering further the consistency of the temperature functions of the theoretical viscosity values for the helium and argon pair potentials, the performance of our all-quartz oscillating-disk viscometer is well established.…”
Section: Methodssupporting
confidence: 77%
See 4 more Smart Citations
“…In addition, a comparison of our experimental argon data between 291 K and 682 K [8] and of experimental reference values obtained by May et al [19] at NIST (203 K to 394 K) with the theoretical argon values [12] showed excellent agreement within ±0.1 %. Considering further the consistency of the temperature functions of the theoretical viscosity values for the helium and argon pair potentials, the performance of our all-quartz oscillating-disk viscometer is well established.…”
Section: Methodssupporting
confidence: 77%
“…The principal difference between the old reference values for helium used for the calibration in our earlier measurements on nitrogen in 1984 [20,21] [16]. According to the sound error analysis in References [8,15], the relative uncertainty of the measurements with our all-quartz oscillating-disk viscometer is conservatively estimated to be ±0.15 % at room temperature and up to ±0.20 % at higher temperatures assuming that the uncertainty could be slightly increased with temperature. The total uncertainty in the viscosity, which additionally includes the allocation errors of the temperature and density measurements considering the temperature and density dependencies of the viscosity, corresponds practically to the uncertainty of the viscosity measurements alone, as the contributions of the allocation errors are negligibly small.…”
Section: Methodsmentioning
confidence: 93%
See 3 more Smart Citations